Intersecções semióticas : a Istambul de Orhan Pamuk e Ara Güler - Moraes, Josiane Borges de (2015)
The goal with this Master s Thesis is the analysis of the hybridism between two distinctive arts, Photography and Literature, especially in Pamuk s Istambul. In this sense, a previous incursion in the world of Photography and its intersections among several literary works will trigger the starting point. Photographers as Marey, Muybridge, Nakaji Yusui, Alfred Stieglitz illustrate the permeable way that the art of writing through light relates to other kinds of art. Duane Michals shows his avant-garde photographic narrative, and Leonardo da Vinci reveals how the art of the numbers works in eye-catching images. As a contribution Roland Barthes sews up the theory of these worlds amongst Susan Sontag, Derrida, Hegel and Benjamin, turning possible a safe landing in Istambul where, in the end, the study about Pamuk s text, which is illustrated with Ara Güler s photographic work, culminates. The search here takes another bias and Sebald helps doing a counterpoint: writing the text with the pictures that were previously chosen versus subsequent choice, that is the way Pamuk does seeking in Güler s Istambul the hüzün eye as genuine as his own.